Useful considerations for the genetic advice of patients with Ebstein anomaly - Odelinda Acosta Camacho; Isabel Marten Powell; Virgen Yaneisy Gross Ochoa; Farah María Kindelán Mercarón (Centro Provincial de Información de Ciencias Médicas, 2020)
Ebstein anomaly is a strange disease that consists on a variable spectrum of anomalies, due to an abnormal installation of the tricuspid valve in the right ventricle; reason why, it is considered a serious and incurable disorder that originates a tendency to the voluntary termination of pregnancy as reproductive option in the mark of prenatal genetic advice. The advances in the diagnosis and clinical surgical control of this disease have guaranteed the increment of survival and a better life quality in these patients. Also, they have allowed to adjust clinical factors that involve its clinical course and prognosis. Some valuations are carried out, in order to provide the necessary arguments that allow the couple to choose an appropriate action course aimed at the risks and family objectives based on the ethical principles of the genetic advice.